1995
DOI: 10.1017/s0954579400006817
|View full text |Cite
|
Sign up to set email alerts
|

The changing importance of romantic relationship involvement to competence from late childhood to late adolescence

Abstract: Although developmental theorists such as Sullivan (1953) and Havighurst (1972) have suggested that the formation of romantic relationships in adolescence is an important developmental task, researchers of the adolescent “problem behavior syndrome” have documented that early sexual intercourse is related to problems with conduct, academics, and chemical use. In this study multiple measures of competence and romantic relationship involvement were obtained from a normative community sample of children and adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 40 publications
7
101
1
6
Order By: Relevance
“…Sexual relationships in early adolescence are associated with an increased risk of social, academic, and behavioral adverse outcomes. 149,150 Research has shown that parents underestimate the likelihood that their child might engage in online conversation with people they do not know. Therefore, it is critical that parents promote online safety with their children from an early age, monitor children's Internet use, and use tools, such as parental control software, to maintain awareness of their child's online activities.…”
Section: Child Pornography and Child Abuse How Has Social Media Changmentioning
confidence: 99%
“…Sexual relationships in early adolescence are associated with an increased risk of social, academic, and behavioral adverse outcomes. 149,150 Research has shown that parents underestimate the likelihood that their child might engage in online conversation with people they do not know. Therefore, it is critical that parents promote online safety with their children from an early age, monitor children's Internet use, and use tools, such as parental control software, to maintain awareness of their child's online activities.…”
Section: Child Pornography and Child Abuse How Has Social Media Changmentioning
confidence: 99%
“…The link almost certainly is mediated by relative psychosocial immaturity and by a general orientation to unconventionality among early active teenagers (Jessor, Costa, Jessor, & Donovan, 1983). As a group, these adolescents tend to be less achievement oriented, more alienated from their parents, and more likely to exhibit other problem behaviors such as drug or alcohol abuse (e.g., Davies & Windle, 2000;Neeman, Hubbard, & Masten, 1995;B. Thomas & Hsiu, 1993;Zimmer-Gembeck et al, 2001).…”
Section: Sexualitymentioning
confidence: 99%
“…In addition to their increasing prevalence, experiences in romantic relationships are important because they can have long-term consequences for adolescent's emotional health [11], social and academic development [12], and selfesteem [13,14]. Numerous scientists have argued that the seeds of healthy adult relationships are sewn in adolescent romantic relationships [15][16][17][18].…”
Section: The Importance Of Studying Adolescent Romantic Relationshipsmentioning
confidence: 99%